Cancer Pain Management in French-Speaking African Countries : Assessment of the Current Situation and Research into Factors Limiting Treatment and Access to Strong Opioid Analgesic Drugs - (:unkn) unknown (My University, 2024)
Introduction :Inadequate control of cancer pain represents an escalating public health concern in Africa, particularly within francophone regions, amidst a concurrent surge in cancer incidence. This study aims to enhance comprehension of the impediments to effective cancer pain management utilizing opioid analgesics in francophone Africa which is sparsely documented in the scientific literature compared to the rest of the world, particularly in the English-speaking countries. Methods : A double phased Survey engaged experts and field clinicians specialized in cancer pain management : 1) Expert questionnaire : a contemporary assessment of the organizational, legislative, and societal landscape at the national or regional scale; 2) Clinician questionnaire : an exploration of practices, identified needs, perceived barriers, and strategies to improve Pain management at local level. Results. A cohort of twelve experts and sixty clinicians from 15 countries diligently completed the surveys. A robust consensus emerged delineating four primary barriers: insufficient human resources with requisite competencies and dedicated facilities, constraints entailing opioid analgesic prescription, limited drug availability compounded by challenges in accessibility, and the economic burden borne by patients. Conclusion : Remedying the often-dire scenario in francophone Africa necessitates a multidimensional endeavour. Critical components encompass training in pain management and palliative care and safe opioids prescription, optimizing drug availability, affordability, and distribution networks, formulating clinical recommendations tailored to the specifics of francophone Africa taking in consideration local contexts and socio-cultural aspects, mitigating prescription constraints, and fostering heightened awareness across all pertinent stakeholders while always minimizing the risks related to opioids.
Keywords: African Research